Effetto Placebo. (Milano : Galleria Murnik, 1987)
Abate, Gianantonio ; Amey, Paul ; Brevi, Dario ; Connely, Arch ; Crosa, Andrea ; Giorvelli, Elena ; Innocente ; Jenskins, Kiely ; Lanigan Schmidt, Thomas ; Lodola, Marco ; Luraschi, Battista ; Melotti, Gianni ; Noua, Kacem ; Palmieri, Luciano ; Pavone, Sergio ; Plumcake (Gianni Cella, Romolo Pallotta, Claudio Ragni) ; Porcelli, Antonio ; Zwillinger, Rhonda
Effetto Placebo, Galleria Murnik, Milano, Dal 29 gennaio al 21 marzo 1987
boek